Six-Minute Walk Test and its Correlation with Spirometry in Stable COPD Patients - Krishna, B. Sai; Mohapatra, Amrut Kumar; Behera, Debasis; Jagaty, Suman Kumar; Subhankar, Saswat; Venkataram, Rajesh; Dash, D. P. (Journal of Health and Allied Sciences NU, 2021)
Objectives An impaired exercise tolerance, the main feature in chronic obstructive pulmonary disease (COPD), occurs due to multiple factors. The 6-minute walk test (6MWT) is easy to perform, well-tolerated, and more reflective of activities of daily living. The facility of spirometry is unavailable in many areas of India, where 6MWT can be done easily. This study aims to compare the six-minute walk distance (6MWD) with various demographic, clinical, and spirometry parameters.Materials and Methods A total of 118 consecutive stable COPD patients fitting the criteria were included in the study. Spirometry was performed in these patients before and after giving a short-acting bronchodilator. 6MWT was performed according to the ATS guidelines. All patients underwent the 6MWT after 10 minutes of spirometry. Statistical analysis was done using GraphPad calculator and SPSS 24.0.Statistical Analysis All data were clubbed together in a single Excel chart. Statistical analysis was done using SPSS 24.0. Descriptive data are presented as mean ± standard deviation (SD). Qualitative data are presented as a percentage. Analysis of variance (ANOVA) was used to compare between means. The linear regression model was used to compare between variables. A p-value less than 0.05 was considered significant.Results The majority of the patients were > 60 years of age (mean age = 62.99 ± 6.68 years) and comprised males and females in the ratio 5.9:1. Smoking was determined to be the most important predisposing factor for the development of COPD. There was a significant negative correlation between 6MWD, age, and smoking index (p = 0.0075 and 0.0295 respectively). The 6MWD showed a significant positive correlation with FEV1 (in liters), FEV1 (%), FVC (in liters), and FVC (%). The 6MWD (meters) and % predicted 6MWD showed a significant negative correlation with a drop in SpO2 after the 6MWT (r = –0.36; p = 0.000769, r = –0.3; p = 0.004, respectively).Conclusion 6MWT can be used in cases of COPD where spirometry is unavailable as it correlates significantly with various parameters of the latter.
Keywords: COPD; 6MWT; 6MWD; spirometry